2001
DOI: 10.1111/0021-8294.00033
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Prejudice from Religious Fundamentalism and Right‐Wing Authoritarianism: A Multiple‐Regression Approach

Abstract: In a study designed to investigate the respective roles of religious fundamentalism and right-wing authoritarianism as predictors of prejudice against racial minorities and homosexuals, participants (47 males, 91 females) responded to a series of questionnaire measures of these constructs. Data were analyzed using multiple regression. Consistent with previous research, authoritarianism was a significant and strong positive predictor of both forms of prejudice. With authoritarianism statistically controlled, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
189
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(213 citation statements)
references
References 23 publications
17
189
3
4
Order By: Relevance
“…Although not central to their study, Rowatt et al (2009) reported a positive bivariate association between religion and racial prejudice that became negative in a multivariate model including RWA, which is consistent with previous research (Laythe et al, 2001;Rowatt & Franklin, 2004;Tsang & Rowatt, 2007).These findings suggest a suppression effect of RWA on the association between religion and positive racial attitudes. Specifically, religious individuals should be motivated by religious teachings to engage in pro-social behaviour (e.g., Pichon, Boccato & Saroglou, 2007;Shariff & Norenzayan, 2007), but also be motivated by authoritarian values to engage in prejudice in order to maintain cohesion and security (Hall et al, 2010;Hoverd & Sibley, 2010).…”
Section: Religious Ambivalencesupporting
confidence: 84%
See 1 more Smart Citation
“…Although not central to their study, Rowatt et al (2009) reported a positive bivariate association between religion and racial prejudice that became negative in a multivariate model including RWA, which is consistent with previous research (Laythe et al, 2001;Rowatt & Franklin, 2004;Tsang & Rowatt, 2007).These findings suggest a suppression effect of RWA on the association between religion and positive racial attitudes. Specifically, religious individuals should be motivated by religious teachings to engage in pro-social behaviour (e.g., Pichon, Boccato & Saroglou, 2007;Shariff & Norenzayan, 2007), but also be motivated by authoritarian values to engage in prejudice in order to maintain cohesion and security (Hall et al, 2010;Hoverd & Sibley, 2010).…”
Section: Religious Ambivalencesupporting
confidence: 84%
“…Religion is certainly linked to authoritarianism, as well as to prejudice (Altemeyer & Hunsberger, 1992;Hunsberger, Owusu & Duck, 1999;Laythe, Finkel, Bringle & Kirkpatrick, 2002;Laythe, Finkel & Kirkpatrick, 2001;Rowatt & Franklin, 2004;Wylie & Forest, 1992). Moulian (1979), for example, discussed the use of religion by authoritarian regimes to rally followers and to justify their actions, and RWA (but not SDO) has been shown to predict support for religious education in public school curriculums .…”
Section: Religious Ambivalencementioning
confidence: 99%
“…This is the important implication of several studies which consider the impact of an individual's Christian fundamentalism and right-wing authoritarianism (RWA; Altemeyer, 1981Altemeyer, , 1988Altemeyer, , 1996 on racial prejudice and homosexual prejudice (e.g., Laythe, Finkel, Bringle, & Kirkpatrick, 2002;Laythe, Finkel, & Kirkpatrick, 2001;Rowatt & Franklin, 2004). Both fundamentalism and RWA typically have positive zero-order correlations with prejudice.…”
Section: Introductionmentioning
confidence: 99%
“…RWA is sometimes distinguished conceptually from a related construct, social dominance orientation, with the former focusing on submission to in-group authority figures and the latter focusing on dominance over out-group members [41,42]. Several studies show RWA to be a precursor to prejudice against racial [43] and sexual [44] minorities, as well as greater emphasis on obedience and punishment in child-rearing practices [45]. Unsurprisingly, RWA is related to conservative political ideology, perhaps because it emphasizes the utility of conventionalism and order as responses to vulnerability [46].…”
Section: Linking Loneliness To Conservatismmentioning
confidence: 99%